Identification of Two Novel Compound Heterozygous EIF2AK3 Mutations Underlying Wolcott–Rallison Syndrome in a Chinese Family - Zhao, Na; Yang, Yanling; Li, Ping; Xiong, Qiuhong; Xiao, Han; Wu, Changxin (Frontiers in Pediatrics, 2021)
Objective Wolcott-Rallison syndrome is a rare autosomal recessive inheritance disorder caused by the defectiveness of eukaryotic translation initiation factor 2 alpha kinase 3 (EIF2AK3) which encodes the PKR-like endoplasmic reticulum kinase (PERK). Defect in EIF2AK3 results in a permanent diabetes in early infancy or newborn period, a tendency to skeletal fractures and other associated disorders such as severe liver and renal dysfunction, and central hypothyroidism. Two patients with Wolcott-Rallison syndrome like manifestations in a Chinese family and family members were genetically analyzed to identify if any variations occurred in EIF2AK3, which may cause Wolcott-Rallison syndrome. Methods Whole-exome sequencing (WES) was performed to identify the genetic variations and the Sanger sequencing was conducted to verify the identified variations in the family members with WRS clinical manifestations. Several bioinformatics tools were employed to predict the effect of EIF2AK3 variations on the protein function. The impact on PERK protein was analyzed by sequential analysis and evolution conservation study. Results Two novel EIF2AK3 heterozygous single base variations (c.2818C>T, and c.2980G>C) were detected in the proband. PERK has two functional domains, one is regulatory domain (aa 1-576), and the other is catalytic domain (aa 577-1115). Both variations are missense mutations and locate in catalytic domain of PERK, c.2818C>T resulted in a residue substitution of proline for serine at amino acid site 940 (p.Pro940Ser), and variation c.2980G>C caused an amino acid change at position 994 from glutamic acid to glutanine (p.Glu994Gln). These novel missense variations may affect the physiological functions of PERK protein. Conclusions Two novel compound heterozygous EIF2AK3 variations (c.2818C>T, p.Pro940Ser and c.2980G>C, p.Glu994Gln) were found in a Chinese family. The identification of the variations and verification of their pathogenicity extended the variation spectrum of EIF2AK3 variations causing Wolcott-Rallison syndrome, meanwhile, enriched valuable information to precise medical intervention for Wolcott-Rallison syndrome in China.